inggris inggris - Hapsari, Pauline; Darodjat; Kusumawinakhyu, Titik (Psikis : Jurnal Psikologi Islami, 2024)
All Muslims look toward the Quran for spiritual and moral direction. Since 1400 years ago, Al-Quran has stated its role as a treatment and therapy for human illness through the term of Syifa. The purpose of this study was to examine important other choice spiritual therapeutic verses in the Quran and determine the parts (juz) and verses (ayaat) where keywords and phrases pertinent to the Quran as a medication for every illness are stated. Currently, Islamic medicine is used as a therapeutic treatment for both physical and mental illnesses. Islamic medicine practitioners usually incorporate specific Quranic verses into their treatment through a variety of methods. This study uses the systematic review approach to gather information from the texts of previous and current scholars and then analyzes the data using a PRISMA methodology. Through comprehensive study among mufassiriin and modern experiments, Quranic verses have had great impact as a treatment or therapy for human ailment, both physically and mentally. As a result, instead of traditional medicine, this technique should be acknowledged and adopted as a supplementary therapy among Muslims.